Strategy for Developing the Quality of Village-Owned Enterprises in Improving Community Business in The Management of Village Economic Potential - Hermansyah, Mamad; Fitriyah, Hadiah (Apollo: Journal of Tourism and Business, 2025)
The purpose of this study is to determine the strategy and development of village businesses to improve the welfare of the community in Kedungbanteng Village, Tanggulangin District, Sidoarjo Regency. The method that has been used in this research is descriptive research methodology with a qualitative approach. The results showed that Kedungbanteng Village in Tanggulangin District, Sidoarjo Regency realized the benefits of developing a Village-Owned Enterprise (BUMDes). That is, by strengthening existing knowledge, the community can improve its products and increase its welfare. In addition, it encourages community development and has a direct impact on the economy and culture. This research was conducted using the tetrapreneur model.